Improvement of thermal stability and flame retardancy of polypolypropylene composite modified by ZnO and MoO3 nanowires. Issue 4 (31st July 2019) - Guo, Junhong; Liu, Guotian; Guo, Yongliang; Tian, Li; Bao, Xuemei; Zhang, Xiujun; Yang, Baoping; Cui, Jinfeng
ABSTRACT: Herein, zinc oxide (ZnO) and molybdenum trioxide (MoO3 ) nanowires were prepared via the hydrothermal method. Then as‐prepared ZnO and MoO3 nanowires were fabricated to form ZnO/MoO3 compound nanostructure. ZnO/MoO3 compounds were incorporated into polypropylene (PP) with various loadings by melt blending. The D‐Optimal mixing design in Design‐Expert software was employed to study the effects of ZnO/MoO3 compound content on flame retardancy and mechanical properties of nanocomposites. Information on performance of thermal stability and flame retardancy of PP/ZnO/MoO3 nanocomposites was obtained through thermogravimetric analysis, cone calorimeter tests, and limiting oxygen index (LOI). The results reflected that the synthesized ZnO/MoO3 compound possessed high thermal stability and flame retardancy. The addition of 15 wt % ZnO nanowires and 13 wt % MoO3 nanowires increased LOI from 18.2 to 23.0%. Meanwhile, the tensile strength of the PP/ZnO/MoO3 nanocomposite decreased by 13.8% and the elongation at break of the PP nanocomposite increased by 20.4% compared with pure PP. Response surface analysis results also indicated that the loading of ZnO/MoO3 compound had an influence on the mechanical properties and flame retardancy of PP. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48312. Abstract :